“O estrangeiro”: enredos imaginados sobre a solidão em Carl Schlichthorst, Carl Seidler e François Biard - Marina Haizenreder Ertzogue (Nuevo mundo - Mundos Nuevos, 2008)
This article covers the journey of three travelers across Brazil in the mid-19th century: Carl Schlichthorst, Carl Seidler and François Biard. From this perspective, the foreigner appears as a spectator of a new self-constructed scenario, revealing himself through his most intimate feeling: loneliness. This text develops a study of sensibilities, involving the realms of the imaginary, literature and history.